2022
DOI: 10.3390/cells11203198
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase: A Novel Therapeutic Target for the Treatment of Atherosclerosis

Abstract: Cardiovascular disease (CVD) is the leading cause of death and disability worldwide, and its management places a huge burden on healthcare systems through hospitalisation and treatment. Atherosclerosis is a chronic inflammatory disease of the arterial wall resulting in the formation of lipid-rich, fibrotic plaques under the subendothelium and is a key contributor to the development of CVD. As such, a detailed understanding of the mechanisms involved in the development of atherosclerosis is urgently required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 226 publications
1
5
0
Order By: Relevance
“…Collectively, we propose that heparanase may function as an epigenetic marker, modulating innate immunity and other cellular functions, in part by controlling gene expression. Given that heparanase is a well-recognized target for inhibition of cancer progression and inflammation [ 43 , 47 ], our findings further strengthen this notion by broadening the multitasking molecular function of the heparanase gene and protein.…”
Section: Discussionsupporting
confidence: 73%
“…Collectively, we propose that heparanase may function as an epigenetic marker, modulating innate immunity and other cellular functions, in part by controlling gene expression. Given that heparanase is a well-recognized target for inhibition of cancer progression and inflammation [ 43 , 47 ], our findings further strengthen this notion by broadening the multitasking molecular function of the heparanase gene and protein.…”
Section: Discussionsupporting
confidence: 73%
“…Recent evidence suggests a multifactorial role for HPSE in atherosclerosis by promoting underlying inflammatory processes giving rise to plaque formation, as well as regulating lesion stability. 21 HPSE also plays a procoagulant role in several arterial and venous thrombotic diseases. 22 The subsequent study demonstrated that elevated HPSE levels were associated with higher thrombus load and rates of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 97 While most studies emphasize the involvement of heparanase in cancer and inflammation, other pathologies were investigated. Among these are diabetes, 74 , 75 diabetic complications (i.e., diabetic nephropathy, diabetic cardiomyopathy), 76 , 77 kidney dysfunction, 182 fibrosis, 78 , 183 inflammatory disorders (i.e., neuroinflammation, pancreatitis, ulcerative colitis, arthritis, sepsis), 59 , 60 , 184 , 185 amyloidosis, 61 atherosclerosis, 66 , 68 , 69 , 70 viral diseases, 96 , 97 and other pathologies. 11 , 12 , 97 Heparanase accomplishes all these by exerting both enzymatic and nonenzymatic functions that are mostly HS‐dependent yet in some cases are HS‐independent.…”
Section: Discussionmentioning
confidence: 99%